Pattern, First Aid and Complications of Snake Bite in Sudan - Ahmed, Imad eldeen O.; Abdalla, Awad R. (مجلة الجزيرة للعلوم الصحية; مجلد 9 عدد 2 (2013), 2013)
Aim: This study aimed at assessing the first aid management and types of complications arising from snakebite. Patients and methods:   A survey of snakebites cases admitted to Sinnar Teaching Hospital, Sinnar, Sudan was conducted between March 2011 and March 2013. The demographic and clinical details of each case were obtained using a questionnaire design to collect primary data from patients and their relatives and patient’s, while, secondary data was collected from the hospital record. Data was analyzed using frequency tabulation. Results: A total number of 111 cases of snake bites were reported during the period of study. The most common age group affected was 19-36 years. The highest number of incidents occurred during daytime from July to December, and lower limb was the major affected part of the body. 41.1% of the victims were farmers. Tourniquet was found to be the most commonly used first aid.  The major observed complications were cellulitis and spontaneous bleeding.  A mortality rate of 3.6% was reported. Conclusion: Extensive use of tourniquet as a first aid measure is one of the primary causes of complications from snakebite. Correct first aid and scientifically based medical intervention are very important snakebite management mechanism and can reduce its complications considerably. Aim: This study aimed at assessing the first aid management and types of complications arising from snakebite. Patients and methods:   A survey of snakebites cases admitted to Sinnar Teaching Hospital, Sinnar, Sudan was conducted between March 2011 and March 2013. The demographic and clinical details of each case were obtained using a questionnaire design to collect primary data from patients and their relatives and patient’s, while, secondary data was collected from the hospital record. Data was analyzed using frequency tabulation. Results: A total number of 111 cases of snake bites were reported during the period of study. The most common age group affected was 19-36 years. The highest number of incidents occurred during daytime from July to December, and lower limb was the major affected part of the body. 41.1% of the victims were farmers. Tourniquet was found to be the most commonly used first aid.  The major observed complications were cellulitis and spontaneous bleeding.  A mortality rate of 3.6% was reported. Conclusion: Extensive use of tourniquet as a first aid measure is one of the primary causes of complications from snakebite. Correct first aid and scientifically based medical intervention are very important snakebite management mechanism and can reduce its complications considerably.